Analisis Laporan Realisasi Anggaran untuk Menilai Kinerja Keuangan Pemerintah Kabupaten Trenggalek Tahun Anggaran 2020 - 2022 - Arini, Arini; Loekman, Zulvianira (Politeknik Negeri Bengkalis, 2024)
Regional governments are obliged to prepare Regional Government Financial Reports (LKPD) as a form of accountability for regional financial management. One component of the LKPD is the Budget Realization Report (LRA) which contains a number of financial information. This research aims to measure the financial performance of the Trenggalek Regency Government through analysis of the Trenggalek Regency Government's LRA for the 2020 - 2022 fiscal year. This research uses a quantitative descriptive analysis method by observing a number of financial ratios. The financial ratios observed in this research include the regional financial independence ratio, effectiveness ratio, efficiency ratio, and regional spending harmony ratio (activity ratio). The regional expenditure compatibility ratio consists of the compatibility ratio of operating expenditure to regional expenditure and the compatibility ratio of capital expenditure to regional expenditure. The results of the analysis show that the financial performance of the Trenggalek Regency Government for the 2020 - 2022 Fiscal Year based on the financial independence ratio has very low financial capacity and has an instructive relationship pattern. Based on the PAD effectiveness ratio, the Trenggalek Regency Government's financial performance is included in the quite effective category. Based on the efficiency ratio in obtaining PAD, the Trenggalek Regency Government is classified as very efficient. Meanwhile, according to the regional expenditure harmony ratio, the Trenggalek Regency Government tends to prioritize operational or routine expenditure over capital expenditure.Keywords: Budget Realization Report, Financial Performance, Financial Ratios